Predicting Heterotopic Ossification Early After Burn Injuries: A Risk Scoring System - Schneider, Jeffrey C; Simko, Laura C; Goldstein, Richard; Shie, Vivian L; Chernack, Betty; Levi, Benjamin; Jayakumar, Prakash; Kowalske, Karen J; Herndon, David N; Gibran, Nicole S; Ryan, Colleen M (Annals of surgery, 2017)
The purpose of this study is to develop a scoring system that stratifies burn patients at the time of hospital admission according to risk of developing heterotopic ossification (HO). HO in burns is an uncommon but severely debilitating problem with a poorly understood mechanism and no fully effective prophylactic measures. Data were obtained from the Burn Model System National Database from 1994 to 2010 (n = 3693). The primary outcome is diagnosis of HO at hospital discharge. Logistic regression analysis was used to determine significant demographic and medical predictors of HO. A risk scoring system was created in which point values were assigned to predictive factors and final risk score is correlated with the percent risk of developing HO. The model was internally and externally validated. The mean age of the subjects is 42.5 ± 16.0 years, the mean total body surface area (TBSA) burned is 18.5 ± 16.4%, and the population is 74.9% male. TBSA and the need for grafting of the arm, head/neck, and trunk were significant predictors of HO development (P < 0.01). A 13-point risk scoring system was developed using these significant predictors. The model c-statistic is 0.92. The risk scoring system demonstrated evidence of internal and external validity. An online calculator was developed to facilitate translation of knowledge to practice and research. This HO risk scoring system identifies high-risk burn patients suitable for diagnostic testing and interventional HO prophylaxis trials.